Pendidikan Karakter Dalam Satua Anak Agung Di Mesir - A. A. Diah Indrayani; I Kadek Widiantana (Cetta: Jurnal Ilmu Pendidikan, 2020)
Over the past few years, the government has given a spesific attention to the character education due to its main purpose to develop good and right behaviour for the students since their early age. To achieve this, one of them is through education. In Bali, according to the concept of its society, education is translated by local values in a simple way, such as learning while travelling, learning while singing, learning while playing a game and so on. The Balinese folklore (Satua) is an implementation of Hindu values which give an understanding on conscience and behaviour to the children since early age. This research is a qualitative research using the hermeneutics method. Bali has many literary heritages which are full of the value of character education, one of them is Satua Bali. Among the many Satua that are available, Satua that will be used is Satua I Nengah Tinggen's with titled Anak Agung di Mesir. He is one of the Balinese literary maestros. The study of this folklore refers to six pillars of character proposed by SD Westwood, covers trustworthiness, respect, responsibility, caring, citizenship, and fairness. It can be concluded that Satua is somewhat effectively used as a character education media because it contains the values ​​of character education needed for the nation's character development and can be taught early with Satua.